Level of satisfaction with family life marriage migrants in South Korea: influence factors on example of ethnic Koreans in the CIS (Journal of Oriental Studies, 2016)
This article focuses on international marriages of ethnic Koreans and South Korean men who choose foreign brides from different countries, including China, Vietnam, Philippines, etc. Author conducted a survey of a sample of ethnic Korean residents of the CIS, who were married in South Korea. Cultural and ideological aspects of CIS countries make them less suited for international marriages with men in South Korea, which affects their satisfaction with family life.
Keywords: South Korea; CIS; international marriage; contentment